Heart transplantation as salvage therapy for progressive prosthetic valve endocarditis due to methicillin-resistant Staphylococcus epidermidis (MRSE) - Borde, Johannes Paul; Sitaru, Ana Gabriela; Kopp, W. H.; Ruhparwar, Arjang; Ehlermann, Philipp; Lasitschka, Felix; Dalpke, Alexander; Heininger, Alexandra (Journal of cardiothoracic surgery, 2016)
Prosthetic valve endocarditis (PVE) has the highest in-hospital mortality among all cases of infective endocarditis (IE), it is estimated at about 40 %. Orthotopic heart transplantation (OHT) as a measure of last resort, may be considered in selected cases where repeated surgical procedures and conservative efforts have failed to eradicate persistent or recurrent IE. Only few clinical data are available regarding this rare indication for OHT, since active IE has traditionally been considered as a contraindication for OHT.
Gesehen am 14.05.2020